Work-family balance among selected Filipino urban working mothers - Yecla, Toni Grace R. (College of Home Economics, University of the Philippines Diliman, 2015)
The study aimed to determine the meaning of work-family balance as perceived by Filipino urban working mothers. The study also examined the presence of work-family balance among the working mothers and identified the positive and negative factors that contribute to or inhibit the achievement of work-family balance. The effects of the presence and absence of balance were also investigated. An interview schedule and a survey questionnaire were utilized as instruments for the data collection. A total of 17 working mothers from public and private institutions in Metro Manila were purposively chosen to participate in the study. Results show that work-family balance is defined by the mothers as allocating time for family and work, meeting the demands of family and work, having little or no problem in the family and at work, and feeling positive about family and work life. Also, majority of the respondents believe that work-family balance is present in their lives. According to them, the positive and negative factors that affect work-family balance include their qualities as a mother, wife and employee; the kind of support system available at home and at work; the strategies they utilize; the availability and quality of material resources; the kind of company policies; and the nature of their work. Positive effects were seen on the relationships with family members and colleagues, work performance, and personal life of the respondents who have work-family balance. On the other hand, similar life aspects mentioned above were negatively affected by the absence of work-family balance. Recommendations for future studies and for home economics practitioners were provided at the end of the paper.